POLA MEMUSAT: SALAH SATU MODEL KOSMOLOGIS PADA MASA PRASEJARAH DI INDONESIA - Sunarningsih (BRIN, 1999)
In prehistoric times in Indonesia, cosmological models have been found on the building steps and in the decorative pattern of the Nekara area. It can be said that the initial thought (embryo) of the cosmological conception has existed since prehistoric times, which was later developed during the Hindu period. With the advancement of technology and the additional knowledge in the concept, the holy places (temples) were built as replicas of the cosmos with a more magnificent, beautiful, and complete.